2016
DOI: 10.4103/0259-1162.186600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bispectral index versus end-tidal anesthetic gas concentration-guided protocol on time to tracheal extubation for halothane-based general anesthesia

Abstract: Background and Aims:Early extubation is a desirable goal after general anesthesia. Very few studies have compared the effect of bispectral index (BIS) monitoring versus standard end-tidal anesthetic gas (ETAG) concentration monitoring on tracheal extubation time for halothane-based anesthesia. The aim of this study was to compare the effect of BIS versus ETAG-guided anesthesia on time to tracheal extubation for halothane-based anesthesia in general surgical setting.Methods:This was a randomized, controlled dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…2023; 13(6):e140027. measure; however, since there is a few seconds time lag for processing data, a clinical measure, the disappearance of eyelash reflex, was taken to estimate the propofol onset of action as well (28,29). To evaluate the adequacy of anesthesia, episodes of BIS > 60 or straining during intubation or opening the eyes were determined.…”
Section: Discussionmentioning
confidence: 99%
“…2023; 13(6):e140027. measure; however, since there is a few seconds time lag for processing data, a clinical measure, the disappearance of eyelash reflex, was taken to estimate the propofol onset of action as well (28,29). To evaluate the adequacy of anesthesia, episodes of BIS > 60 or straining during intubation or opening the eyes were determined.…”
Section: Discussionmentioning
confidence: 99%
“…However, Jain et al [ 4 ] performed a study with halothane and found contrarily significantly ( P < 0.05) shorter extubation time in the ETAG-guided group (5.29 ± 1.51 min) as compared to BIS-guided group (9.63 ± 3.02 min) (mean difference 4.34 min with 95% confidence interval [3.106, 5.982]). The probable reason may be the inhalational agent used, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was based on assuming a difference of 4.34 min in both groups with 95% confidence interval, 5% alpha error using G-power 3.1 Software [Heinrich Heine University, Dusseldorf, Germany]. [ 4 ] The quantitative variables were compared using unpaired t -test and qualitative variables were compared using the Chi-square/Fisher's exact test. P < 0.05 was considered statistically significant.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%